Identification and functional analysis of the DOF gene family in Populus simonii: implications for development and stress response - Cai, Kewei; Xie, Xiaoyu; Han, Lu; Chen, Junbo; Zhang, Jinwang; Yuan, Hongtao; Shen, Jiajia; Ren, Yishuang; Zhao, Xiyang (Frontiers in Plant Science, 2024)
Background Populus simonii, a notable native tree species in northern China, demonstrates impressive resistance to stress, broad adaptability, and exceptional hybridization potential. DOF family is a class of specific transcription factors that only exist in plants, widely participating in plant growth and development, and also playing an important role in abiotic stress response. To date, there have been no reported studies on the DOF gene family in P. simonii, and the expression levels of this gene family in different tissues of poplar, as well as its expression patterns under cold, heat, and other stress conditions, remain unclear. Methods In this study, DOF gene family were identified from the P. simonii genome, and various bioinformatics data on the DOF gene family, gene structure, gene distribution, promoters and regulatory networks were analyzed. Quantitative real time PCR technology was used to verify the expression patterns of the DOF gene family in different poplar tissues. Results This research initially pinpointed 41 PSDOF genes in P. simonii genome. The chromosomal localization results revealed that the PSDOF genes is unevenly distributed among 19 chromosomes, with the highest number of genes located on chromosomes 4, 5, and 11. A phylogenetic tree was constructed based on the homology between Arabidopsis thaliana and P. simonii, dividing the 41 PSDOF genes into seven subgroups. The expression patterns of PSDOF genes indicated that specific genes are consistently upregulated in various tissues and under different stress conditions, suggesting their pivotal involvement in both plant development and response to stress. Notably, PSDOF35 and PSDOF28 serve as pivotal hubs in the interaction network, playing a unique role in coordinating with other genes within the family. Conclusion The analysis enhances our comprehension of the functions of the DOF gene family in tissue development and stress responses within P. simonii. These findings provide a foundation for future exploration into the biological roles of DOF gene family.